2015
DOI: 10.1089/gtmb.2015.0040
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Diagnosis of Fetal Gender: Utility of CombiningDYS14andSRY

Abstract: Our results show that the test performance improved with the employment of two Y-amplification assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Nearly similar results were achieved by Jacob et al, 2015(84% and 92.8%) [23]. However, higher sensitivity results obtained by Rijnders et al,…”
Section: Discussionsupporting
confidence: 80%
“…Nearly similar results were achieved by Jacob et al, 2015(84% and 92.8%) [23]. However, higher sensitivity results obtained by Rijnders et al,…”
Section: Discussionsupporting
confidence: 80%
“…As seen with other studies, using both genes demonstrated a marked improvement of sexing the fetus [12, 3032]; however, these studies used maternal plasma as the source. To our knowledge, this is one of the first studies to examine the SRY and DYS14 regions to sex an embryo before implantation.…”
Section: Discussionmentioning
confidence: 81%
“…The DYS14 gene can also identify male DNA in a mixture of male and female blood samples (Barra et al 2015) and in a mixture of male and female saliva samples (Kamodyova et al 2013). In a study of non-invasive fetal gender (Jacob et al 2015), the combined use of DYS14 and SRY recognized correctly 100% of samples from male-bearing pregnancy while two male samples with SRY gave false-negative results.…”
Section: Discussionmentioning
confidence: 99%